2020
DOI: 10.18632/aging.104020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of droplet digital PCR for quantification of SARS-CoV-2 Virus in discharged COVID-19 patients

Abstract: The worldwide severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has led to the rapid spread of coronavirus disease (COVID-19). The quantitative real time PCR (qPCR) is widely used as the gold standard for clinical detection of SARS-CoV-2. However, more and more infected patients are relapsing after discharge, which suggests qPCR may fail to detect the virus in some cases. In this study, we selected 74 clinical samples from 43 recovering inpatients for qPCR and Droplet Digital PCR (ddPCR) sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Our finding that measurement using qPCR and ddPCR are highly correlated is consistent with other studies in nasopharyngeal swabs (Falzone et al 2020, Liu et al 2020), plasma (Tedim et al 2021), wastewater from aircraft and cruise ships (Ahmed et al 2020), and raw influent (Cieselski et al 2021). However, we observed that the correlation became weaker at the lower end of the concentration range we tested, spreading out at lower concentrations in a “broom-shaped” pattern consistent with studies comparing measurements of bacterial targets (Cao et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that measurement using qPCR and ddPCR are highly correlated is consistent with other studies in nasopharyngeal swabs (Falzone et al 2020, Liu et al 2020), plasma (Tedim et al 2021), wastewater from aircraft and cruise ships (Ahmed et al 2020), and raw influent (Cieselski et al 2021). However, we observed that the correlation became weaker at the lower end of the concentration range we tested, spreading out at lower concentrations in a “broom-shaped” pattern consistent with studies comparing measurements of bacterial targets (Cao et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, ddPCR is able to accurately assess SARS-CoV-2 viral load, thus allowing clinicians to effectively diagnose COVID-19 infection, particularly in asymptomatic or paucisymptomatic patients ( 188 ). In addition, ddPCR may be used for the monitoring of COVID-19 patients, thus allowing the discharge of patients who have resolved the infection and to guarantee correct social isolation measures useful for limiting the spread of infections ( 189 ).…”
Section: Alternative Methods For the Effective Diagnosis Of Covid-mentioning
confidence: 99%
“…In recent years, digital PCR (dPCR) has emerged as an attractive alternative for environmental applications as it offers absolute quantification without the need for a standard curve, and it may be more sensitive and less prone to inhibition (Cao et al, 2015). As applied to the detection of SARS-CoV-2, RT-dPCR has been reported to be superior to RT-qPCR for clinical specimens, including nasopharyngeal samples (Falzone et al, 2020;Liu et al, 2020;Suo et al, 2020) and plasma from infected patients (Tedim et al, 2021), as it was found to be more sensitive and accurate.…”
Section: Pcr Platformsmentioning
confidence: 99%